Intersecting Axes of Deprivation and Aspiration: An Empirical Dissection of Educational Attainment, Employment Structures, and Poverty Dynamics in the Kashmir Valley: Intersecting Axes of Deprivation and Aspiration: An Empirical Dissection of Educational Attainment, Employment Structures, and Poverty Dynamics in the Kashmir Valley - Asif Bashir; Naseer Ahmad Bhat; Rafia Mushtaq (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This empirical investigation undertakes a granular socio-economic autopsy of the Kashmir Valley, dissecting the multifaceted interplay among educational attainment, employment stratification, and poverty incidence. Drawing upon stratified demographic data, the study interrogates the assumptions that formal education acts as a panacea against economic marginality. Although a discernible inverse correlation between educational level and poverty prevalence is established—most notably, with only one in twenty postgraduates living below the poverty line—the data simultaneously reveal an unsettling incongruity: elevated education does not axiomatically culminate in employment. A pronounced graduate unemployment rate (21.6%) underscores systemic disconnects between academic curricula and localized labor markets. The study illuminates acute gender-based disparities, where female unemployment (39.7%) significantly eclipses male rates, with rural women bearing the brunt of socio-economic exclusion. Informal employment patterns remain entrenched in rural terrains, perpetuating subsistence economies devoid of structural mobility. Urban-rural dichotomies in monthly income (INR 16,400 vs. INR 8,300) reveal infrastructural and opportunity asymmetries, while government employment surfaces as the singular bastion of economic stability and aid-independence. The discussion extrapolates these findings into a broader analytical frame, critiquing policy inertia, aid-dependency paradigms, and educational irrelevance. The study culminates in a set of praxis-oriented recommendations: localized micro-industrialization, curriculum recalibration, gender-responsive economic ecosystems, digital cooperatives, public sector decentralization, youth-focused resilience programs, and geo-spatial equity audits. These interventions collectively aspire to reconfigure the region’s socio-economic architecture from passive dependency toward sustainable empowerment.